DEVELOPMENT OF LINKAGE MODEL FOR MALAYSIAN CONSTRUCTION SECTOR USING TIME SERIES ANALYSIS IN VECTOR ERROR CORRECTION MODEL - KHAN, RAZA ALI (2014)
The construction sector and socioeconomic development are closely associated. The Infrastructure development is essential to achieve the main development targets such as urbanization, industrialization, export promotion, equitable income distribution, and sustainable economic development. It is impossible to develop infrastructure without the help of the construction sector, and without proper infrastructure a country cannot be developed. The purpose of this study is to develop vector error correction model (VECM) equation for construction sector of the Malaysia to analyze the long run and short run association between the Malaysian construction sector (MCS) and other major sectors, namely manufacturing, mining and quarrying, agriculture and forestry and services of the Malaysian economy including gross domestic product (GDP) of Malaysia. The VECM equation is also used to develop impulse response functions (IRFs) to analyze the behavior of the MCS against the positive investment shock produced in other major sectors of the economy and vice versa. Furthermore the estimated model equation for MCS is used to forecast the future output ofMCS from 2014Ql to 2020Q4.